Detection and Propagation of Metadata Updates within CIS environment - Samoilenko, Sergey (Archives of Business Research, 2022)
In order to adapt to the demands of the modern hypercompetitive environment many organizations integrate their information sources and form alliances. Cooperative Information System (CIS) provides a flexible form of integration that requires, due to absence of the common integrated schema, heightened attention to the data quality management. Commonly, the associated with the CIS’ data metadata assumed to be static and of a high quality. However, in a modern fast changing competitive environment this assumption must be relaxed, and the issue of metadata quality management should be addressed explicitly. While research concerning data quality in CIS environment is abundant, no work, to our knowledge, has addressed the issues of how changes to metadata could be detected and propagated within the CIS environment. In this paper we attempt to address this research problem by proposing, first, a metadata update management methodology and, second, a conceptual design of the technical solution allowing for the detection and propagation of metadata updates within CIS environment